Towards universal health coverage: governance and organisational change in ministries of health - Berman, Peter (BMJ Glob Health, 2019)
Countries have implemented a range of reforms in health financing and provision to advance towards universal health coverage (UHC). These reforms often change the role of a ministry of health (MOH) in traditionally unitary national health service systems. An exploratory comparative case study of four upper middle-income and high-income countries provides insights into how these reforms in pursuit of UHC are likely to affect health governance and the organisational functioning of an MOH accustomed to controlling the financing and delivery of healthcare. These reforms often do not result in simple transfers of responsibility from MOH to other actors in the health system. The resulting configuration of responsibilities and organisational changes within a health system is specific to the capacities within the health system and the sociopolitical context. Formal prescriptions that accompany reform proposals often do not fully represent what actually takes place. An MOH may retain considerable influence in financing and delivery even when reforms appear to formally shift those powers to other organisational units. MOHs have limited ability to independently achieve fundamental system restructuring in health systems that are strongly subject to public sector rules and policies. Our comparative study shows that within these constraints, MOHs can drive organisational change through four mechanisms: establishing a high-level interministerial team to provide political commitment and reduce institutional barriers; establishing an MOH ‘change team’ to lead implementation of organisational change; securing key components of systemic change through legislation; and leveraging emerging political change windows of opportunity for the introduction of health reforms.